Evaluation of web-based self-assessment module administered in a medical school of Nepal - Bhandary, Shital; Ghimire, Satish Raj; Shrestha, Ira (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Self-assessment enables medical students to self-evaluate their knowledge and seek timely assistance for effective learning from their peers and faculties. Self-assessment is an integral part of the student assessment system of School of Medicine, Patan Academy of Health Sciences.Methods: Multiple Choice Questions (MCQs) and Structured Integrated Short Answer Questions (SISAQs) links were sent to the personal e-mail of medical students at the start of Principle of Human Biology I Block. These items were created and selected from various disciplines as per their curricular weightage in this block. Students’ scores and feedback were analysed once this 11-week long block was over.Results: The MCQ surveys had ideal difficulty levels and acceptable discrimination indices but they had poor internal consistencies. The criterion-referenced cut-scores of MCQs and SISAQ were higher than the conventionally used 50% pass-mark in Nepal. Students’ suggested to increase the MCQs and SISAQ numbers and match them in terms of their difficulty levels with the end-block and end-year summative assessments. Item analysis helped to identify the items to be retained, revised and discarded for the future use.Conclusions: Web-based self-assessment of knowledge was found to be an extremely useful tool to inculcate self-directed and life-long learning habits among medical students.Journal of Patan Academy of Health Sciences. 2014 Dec;1(2):58-63